BOOK REVIEW OF LITTLE LORD FAUNTLEROY WRITTEN BY FRANCES HODGSON BURNETT - NUGROHO, VITO ADI (LANTERN (Journal on English Language, Culture and Literature), 2016)
There are many well-known writers who use their own imaginations of childhood for their novel. Burnett, for example, is a modern novelist in the early twentieth century. Her seventh novel was published by Scribner publisher in October, in 1886, entitled Little Lord Fauntleroy. It is interesting to review Little Lord Fauntleroy since it represents the kindness and ordinary life of a little boy noble who does not only care to his family, but also to the people around.